Locating Portuguese hindus: transnationality in urban settings - Cachado, R. (Sociologia, Problemas e Práticas, 2014)
This paper presents the case of Portuguese Hindu Gujarati families in Lisbon and in Leicester. It aims to corroborate the increasing importance of the urban referential in transnationality studies. Recent approaches in transntionality studies include the significance of cities for transmigrants under a variety of levels. One of them is social mobility. This paper focus specifically in motility, and it confirms, through ethnography, that beyond the classical national referential, the urban referential plays a central role for migration decisions. Cities confirm what transnationality scholars have been aware of: that migrants live and move between cities.